(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The IL28B gene encodes interferon-lambda-3, a cytokine that activates JAK-STAT signaling in hepatocytes and plays a pivotal role in the innate antiviral response against hepatitis C virus (HCV). The rs12979860 C/T polymorphism, first identified through genome-wide association studies, has been consistently linked with both spontaneous viral clearance and treatment-induced sustained virologic response [1]. Even in the current era of direct-acting antivirals, IL28B retains prognostic significance because genetically determined inflammatory intensity affects the rate of fibrogenesis irrespective of virologic outcomes [2]. Eslam M. et al. (2017) demonstrated that the IFNL3 haplotype mediates hepatic inflammation and fibrosis progression independently of viral replication [3]. Population-level data on IL28B allele frequencies in Central Asian cohorts remain limited, which restricts the applicability of existing prediction models to this region.